SYSTEMATIC VARIETY OF THE TYPE CREEPING - SAMREEN JAHAN (International Journal of Multidisciplinary Research and Studies, 2020)
The theory that creep is caused by diffusion-like processes, with sediment flow linearly related to surface slope, is supported by observations made on convex hills, which demonstrate that soil thickness decreases with increasing topographic curvature Such movement of individual soil grains could be caused by burrowing creatures (such as worms, ants, and gophers) and by tree throw (trees that have been uprooted, typically by high winds, often carry soil and bedrock attached to the root wad), coupled with localized slope wash; however, field observations and laboratory studies show that nondiffusive processes, such as shear and depth-dependent viscous-like flow, may also occur. Burrowing creatures are examples of such organism. In addition, the observed connections between soil depth and slope curvature on linear and compound slopes are not consistent with a straightforward linear relationship between sediment flow and surface slope alone.